Tiny – optimised 3D mesh NoC for area and latency minimisation. Issue 3 (1st January 2014) - Marcon, C.; Webber, T.; Fernandes, R.; Cataldo, R.; Grando, F.; Poehls, L.; Benso, A.
Abstract : Tiny is a scalable and efficient three‐dimensional (3D) network‐on‐chip (NoC) designed to reduce latency and area. A theoretical analysis demonstrates its efficiency when compared with a basic 3D mesh NoC. Mapping independent traffics with different injection rates makes the trade‐offs analysis of Tiny possible. Results highlight that Tiny always reduces area and for several cases minimises latency.